USE OF ROLE-PLAYING GAMES IN ENGLISH LESSONS (Conferencea, 2022)
this article is devoted to the method of using role-playing games in the process of teaching foreign languages to children.This article focuses on the impact of this method on children, as well as the purpose of this method.Today, this method is widely used in many educational institutions. So what is the purpose of this?I tried to answer these questions in as much detail as I could